Characterising the use, users and effects of a health app supporting lifestyle changes in pregnant women - Koivuniemi Ella; Raats Monique M; Ollila Helena; Löyttyniemi Eliisa; Laitinen Kirsi (United Kingdom, 2022)
The study objective was to (1) compare, through a randomised pilot intervention study, the effects of a standard health app and an enhanced health app, with evidence-based information regarding healthy lifestyle, on gestational weight gain, diet quality and physical activity in pregnant women. The sub-objectives were to (2) characterise app use and users among pregnant women and to (3) compare, in the overall sample regardless of the intervention, whether the frequency of the health app use has an effect on the change in gestational weight, diet quality and physical activity. Women recruited through social media announcements (n 1038) were asked to record their lifestyle habits in the app from early pregnancy to delivery. Self-reported weight, diet quality and physical activity were assessed in early and late pregnancy with validated online questionnaires. No benefits of the enhanced app use were shown on the lifestyle habits. Nevertheless, frequent app users (use ≥ 4·7 weeks) in the enhanced app group had a higher physical activity level in late pregnancy compared with those in the standard app group. Overall, extensive variation was found in the number of recordings (median 59, interquartile range 19-294) and duration of app use (median 4·7, interquartile range 1·1-15·6 weeks). Frequent app users had higher education level, underweight/normal weight, better diet quality and were non-smokers, married and primipara more likely than occasional app users/non-users. Physical activity among app users decreased less compared with non-users over the pregnancy course, indicating that app use could motivate to maintain physical activity during pregnancy.